Measuring and explaining large‐scale distribution of functional and phylogenetic diversity in birds: separating ecological drivers from methodological choices. Issue 6 (17th February 2014) - Calba, Sarah; Maris, Virginie; Devictor, Vincent
Abstract Aim Investigations into how different facets of biodiversity are related has become a central research agenda in ecology. Here, we use a large‐scale and high‐resolution data set on bird distribution to examine the robustness of the relationships between species diversity and functional or phylogenetic diversity. Location France Methods We measured the functional and phylogenetic diversity of 1914 bird assemblages monitored over 10 years with a standardized protocol. We investigated the consequences of incorporating abundance versus presence–absence data, changing the number and identity of traits considered, or varying the spatial scale used to estimate functional and phylogenetic diversity. We further examined the outcomes of different null model procedures that aim to reveal ecological processes influencing the distribution of each facet of diversity. Results We found that the shape and strength of the relationship between species diversity and functional diversity are structured by several methodological choices. We show that increasing the quantity of information yielded by the indices (in particular, including abundances or increasing the number of traits considered) decreases the amount of functional redundancy estimated. Reducing the number of functional traits used to estimate functional diversity can change and even reverse the relationship of interest. Moreover, using alternative null models, we highlighted the specific role of environmental filtering and the link between species abundances and their functional originality (defined for a given species as the average of the functional distances with other species). The same tests applied to phylogenetic diversity revealed that its relationship with species diversity varies differently suggesting that this latter index cannot be used as a proxy for functional diversity. Main conclusions Our results show that the identification of patterns and processes linking species diversity to functional or phylogenetic diversity vary with methodological choices. We further show that the study of these sources of variation via robustness tests allows ecologically meaningful information to be separated from pure artefacts.